Competing hydrostatic compression mechanisms in nickel cyanide - Adamson,J; Lucas,TC; Cairns,AB; Funnell,NP; Tucker,MG; Kleppe,AK; Hriljac,JA; Goodwin,AL (Physica B: Condensed Matter, 2015)
We use variable-pressure neutron and X-ray diffraction measurements to determine the uniaxial and bulk compressibilities of nickel(II) cyanide, Ni(CN)2. Whereas other layered molecular framework materials are known to exhibit negative area compressibility, we find that Ni(CN)2 does not. We attribute this difference to the existence of low-energy in-plane tilt modes that provide a pressure-activated mechanism for layer contraction. The experimental bulk modulus we measure is about four times lower than that reported elsewhere on the basis of density functional theory methods [Phys. Rev. B 83 (2011) 024301].